2017
DOI: 10.1111/dmcn.13412
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after scoliosis surgery for children with cerebral palsy: a systematic review

Abstract: Limited high-quality evidence exists for outcomes after scoliosis surgery in children with CP, a procedure associated with a moderately high complication rate. The intervention appears indicated for deformity correction, but currently there is insufficient evidence to make recommendations for this surgery as a way to also improve functional outcomes, caregiver outcomes, and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 72 publications
0
23
0
2
Order By: Relevance
“…The risk of pulmonary problems in neuromuscular patients following spinal surgery is well known and includes respiratory failure, aspiration, pneumonia, pneumothorax, or pleural effusion [ 2 , 6 , 7 ]. Rates between 17 and 50% have been reported in the literature [ 6 9 ]. Scoliosis surgery has been shown to produce a transient decrease in vital capacity in all patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of pulmonary problems in neuromuscular patients following spinal surgery is well known and includes respiratory failure, aspiration, pneumonia, pneumothorax, or pleural effusion [ 2 , 6 , 7 ]. Rates between 17 and 50% have been reported in the literature [ 6 9 ]. Scoliosis surgery has been shown to produce a transient decrease in vital capacity in all patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review concluded that there is only limited high‐quality evidence for outcomes after scoliosis surgery in children with CP and that this procedure is associated with a moderately high complication rate. The intervention appears to be indicated for deformity correction, but currently there is insufficient evidence to make recommendations for this surgery as a way to also improve functional outcomes, caregiver outcomes, and quality of life . Another complication of these and other orthopaedic complications is chronic pain, which is highly prevalent in children with CP in a high GMFCS level .…”
Section: Recurrent Aspirationmentioning
confidence: 99%
“…The intervention appears to be indicated for deformity correction, but currently there is insufficient evidence to make recommendations for this surgery as a way to also improve functional outcomes, caregiver outcomes, and quality of life. 48 Another complication of these and other orthopaedic complications is chronic pain, which is highly prevalent in children with CP in a high GMFCS level. 49 The impact of chronic pain on the respiratory system, including the effects of analgesics, remains to be studied.…”
Section: Deformity Of the Spine And Chest Wallmentioning
confidence: 99%
“…Additional risk factors for scoliosis include being female, having undergone hip surgery, moderate to severe epilepsy, poor muscle control, muscle weakness and spasticity . Treatment modalities for scoliosis can be either surgical (segmental spinal fusion) or nonsurgical (spinal bracing) . Although surgery appears indicated for deformity correction, in a recent review article, insufficient evidence in terms of functional outcomes, caregiver outcomes and quality of life were reported …”
Section: Introductionmentioning
confidence: 99%
“…Treatment modalities for scoliosis can be either surgical (segmental spinal fusion) or nonsurgical (spinal bracing) . Although surgery appears indicated for deformity correction, in a recent review article, insufficient evidence in terms of functional outcomes, caregiver outcomes and quality of life were reported …”
Section: Introductionmentioning
confidence: 99%